TRENDS AND PERSPECTIVES OF AGRICULTURAL DEVELOPMENT IN SERBIA - Aničić, Dušan; Nestorović, Olgica; Aničić, Jugoslav; Jovanović, Zoran (Economics of Agriculture, 2025)
In the modern global environment, there is a trend of increasing and changing the structure of demand for agricultural sector products. This situation requires a market-oriented approach from agricultural producers, ranging from economic entities to individual farms. Serbia’s agricultural policy is characterized by short-term, ad hoc measures, which prevent predictions and timely adjustments by producers, leaving participants in the market chain uncertain about their long-term orientation. In the total value of agricultural production in 2023, crop production accounted for 69.8%, while livestock production accounted for 30.2%, whereas in developed EU countries, the ratio of crop to livestock production is reversed. This indicates a significant share of low-value-added production, or production with a low level of processing. This paper analyzes the state of Serbia’s agricultural sector, which is under pressure from poor agricultural policies, numerous internal weaknesses, and insufficient financial resources in an unstable geopolitical environment.